DAIRY FARMING AND ITS PREVALENCE IN INDIA: BREAD EARNER FOR THE FARMERS - et. al., Dr. Monoo John (International Journal of Modern Agriculture, 2021)
In India, dairy farming has the ability to provide farmers with extra income along with achieving significant dairy farming objectives, i.e. diversified production and fostering the ecological cycle within the agricultural system. India is currently the world's largest milk producer, backed by an astonishing growth rate in the milk industry. In addition to this, there has been an increased concern about the safety of milk and milk products, including pollution, toxins and the residual effects of various chemical products, due to increasing market understanding. As an alternative option, interest in dairy farming is growing globally at a fast rate. A sharp growth in demand for milk and milk products has been seen in recent years. The paper addressed milk farming in India and explains how India has been prevalent since time immemorial, India resolution, Dairy Farming Investment and Dairy Farming Breed Collection. The rapid expansion of dairy farming under Indian conditions is possible due to certain primary geographical, cultural and economic benefits, such as conventional agriculture and indigenous technological expertise and practices practiced by Indian farmers, etc. But the prevalence of small and marginal dairy farmers still raises many obstacles, along with several other shortcomings, to the faster proliferation of dairy farming.